Empirical correlations for sizing adiabatic capillary tubes using conventional refrigerants and their alternatives - Sulaimon, Shodiya (Begell House Inc, 2015)
This paper presents new empirical correlations developed by using conventional and alternative refrigerants for determining the size of adiabatic capillary tubes used in small vapor compression refrigeration systems. A homogenous two-phase flow model based on the principal equations of conservation of mass, momentum, and energy has been developed. Colebrook's and Churchill's formulations were used to determine the single-phase friction factor. Also, the two-phase viscosity models of Cicchitti et al. (1960), Dukler et al. (1964), McAdam et al. (1942), and Lin et al. (1991) were used to determine the two-phase viscosity factor. The developed numerical model that takes account of a metastable process to enhance the model was validated by using experimental data from the literature with an average error of 1.75%. This developed model that had not been employed previously by researchers was used to study the effects of relevant parameters on the capillary tube length. From these effects, empirical correlations of the capillary tube length with these dependent variables have been developed. Comparing the empirical models with experimental data from the literature showed a reasonable agreement with an average error of 3.45%. Though the empirical model developed in this study covers a large set of refrigerants, it should be used with caution by considering the range of operating conditions covered.